2015
DOI: 10.1093/abbs/gmv033
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase 1 inhibition prevents interleukin-1β-induced inflammation in human osteoarthritic chondrocytes

Abstract: Osteoarthritis (OA) is an age-related joint disease that is characterized by the degeneration of articular chondrocytes. Nuclear enzyme poly(ADP-ribose) polymerase 1 (PARP-1) is associated with inflammation response. We investigated the role of PARP-1 in interleukin-1β (IL-1β)-stimulated human articular chondrocytes and its underlying mechanism. Cell viability and apoptosis were evaluated by using 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-di-phenytetrazoliumromide assay and flow cytometry, respectively. Tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28]. Furthermore, several studies have investigated the MMP-13 level in osteoarthritis patients, and consistent observation is obtained, whereby the MMP-13 level increased significantly in patients with osteoarthritis [30,48,59,[73][74][75][76][77][78]. MMP-13, as a collagenase, is responsible for the degradation of type II collagen [79], which is the main collagen type in articular cartilage [80].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 68%
See 2 more Smart Citations
“…Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28]. Furthermore, several studies have investigated the MMP-13 level in osteoarthritis patients, and consistent observation is obtained, whereby the MMP-13 level increased significantly in patients with osteoarthritis [30,48,59,[73][74][75][76][77][78]. MMP-13, as a collagenase, is responsible for the degradation of type II collagen [79], which is the main collagen type in articular cartilage [80].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 68%
“…Other than the cytokines aforementioned, several other cytokines are involved in the pathogenesis of osteoarthritis. Some of the cytokines shown to increase in osteoarthritis are IL-18, TGFβ1 [14], IL-1 receptor (IL-1R) [59], and IL-1 alpha (IL-1α) [23]. Shan et al showed enhanced serum IL-21, IL-17A, and IFN-γ levels in patients with osteoarthritis compared to controls [15].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(ADP-ribose) polymerase-1. Poly(ADPribose) polymerase-1 (PARP-1) activation is a major cytotoxic mechanism and plays a key role in the pathogenesis of cardiovascular and inflammatory diseases (Beneke, 2008;Peng et al, 2012;Song et al, 2013;Sun et al, 2015). Emerging data suggest that cell death pathways in ischemic stroke are sexually dimorphic (Reeves et al, 2008;Yuan et al, 2009;Liu et al, 2011;Gibson, 2013).…”
Section: Cell Death Pathwaysmentioning
confidence: 99%
“…PARP inhibitors were tissue-protective in animal models of multiple sclerosis, meningitis, arthritis, stroke, and traumatic brain injury (241,(554)(555)(556)(557)(558)(559)(560). PARP inhibitors reduced neuroinflammation, edema, leukocyte infiltration, and the expression of adhesion proteins (242).…”
Section: Parp Inhibition Has Positive Effects On Inflammatory Responsmentioning
confidence: 99%